Women's vulnerabilities to climate insecurity and violence: Household-level evidence from Bangladesh - Suza, Ma; Warner, Jeroen; Pacillo, Grazia; Läderach, Peter; van Dijk, Han (Wiley, 2025)
This study investigates the often-overlooked interpersonal conflicts within the climate and security nexus, focusing on how climate impact exacerbates women's security risks on Hatiya Island, Bangladesh. While climate security literature typically examines group-level conflicts, such as between farmers and pastoralists or between ethnic groups, this study shifts the focus to intra- and inter-household dynamics, exploring conflicts experienced by women with spouses, family members, and neighbors. Using life history interviews, the study reveals how climate vulnerabilities, economic hardship, and entrenched gender norms heighten tensions, leading to conflicts both within households and among neighboring women in a rural patriarchal social context. The findings suggest that climate-induced economic challenges intensify domestic tensions while land scarcity from coastal erosion and resource degradation fuels disputes among neighboring women. The paper underscores addressing the deep-rooted social norms and institutionalized gender inequalities that deepen women's vulnerabilities to climate impacts in conservative societies like those found in Bangladesh and across large parts of the global South to protect them from violence.